Legenda Kolam Petirtaan di Kabupaten Mojokerto: Kajian Sosiologi Sastra Lisan - Icha Fadhilasari (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
Oral stories in the form of legend which spread in Mojokerto, is one form of oral literature which is inherited from generation to generation. The study of the Legend of Kolam Petirtaan in Mojokerto includes three objects, namely: (1) Kolam Segaran, (2) Kolam Candi Tikus, (3) Kolam Candi Jalatunda. This study aims to find (1) the structure of the Legend of Kolam Petirtaan; Kolam Candi Tikus; and Kolam Candi Jalatunda, (2) the social function of the Legend of Kolam Segaran; Kolam Candi Tikus; and Kolam Candi Jalatunda, and (3) the public trust towards the Legend of Kolam Segaran; Kolam Candi Tikus; and Kolam Candi Jalatunda. This study uses qualitative research methods based on literature and field data. Field data were obtained from data sources in Trowulan Village, Trowulan District, Mojokerto Regency and Seloliman Village, Trawas District, Mojokerto Regency. The location is a legacy of the kingdom of Majapahit and the Kingdom of Kahuripan. Data collection of this study was obtained through observation techniques, interviews, recording, writing, documentation, and transcription. Overall, it can be seen that, the Legend of Kolam Segaran; Kolam Candi Tikus; and Kolam Candi Jalatunda has the structure, social function and valuable public trust and are still trusted by the local community.